Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.